Peran Orang Tua dalam Pendampingan Anak pada Pembelajaran Membaca Awal di Rumah - Sri Rahayuningsih; Diah Wahyuningsih (Lembaga Yasin AlSys, 2026)
Although parental involvement in children’s learning has been widely examined in previous studies, research that specifically addresses home-based early reading assistance strategies and the challenges encountered remains limited. This study aims to describe the role of parents, identify assistance strategies, and analyze the challenges in children’s early reading learning at home. This study used a qualitative approach with a case study design, involving 15 parents of children aged 5–6 years who were selected using purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The results showed that parents served as facilitators, companions, and motivators in the early reading learning process. Assistance strategies were implemented gradually, starting from letter recognition to reading simple words, by utilizing media such as picture books and letter cards. The challenges encountered included children’s low concentration, the emergence of boredom, and parents’ limited time. In addition, the quality of interaction between parents and children was found to have a greater influence than the intensity of assistance. These findings contribute to the development of the concept of family-based early childhood literacy and emphasize the importance of effective parental involvement in supporting children’s early reading skills.